(3YGdejI JLGQI GdbQf GdMGOj hGdYTQjf (B(2) :s (3GdJcJdGJ GdEbJUGOjI GdEbdjejI aj EWGQ GdYhdeI (B/s - (3YHO GdYRHR, SejQ eMeOs ((3GdEScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2006)
(3GdchejSG(B- (3eLehYI (B15 -(3ChQhHG GdehMOI(B- (3GdeTGQcI GdCQhHjI GdEaQjbjI GdeJhSWjI(B- (3efWbI GdJLGQI GdYQHjI GdMQIs
Keywords: (3GdEbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs; (3GdJcJdGJ GdEbJUGOjI (B- (3GdOhdjIs; (3GdYhdeIs